THE IMPACT OF THE COVID-19 PANDEMIC ON THE EDUCATIONAL PROCESS - Hural, Inesa Mykhailivna; Smolovyk, Liana Romanivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The problems and risks that have arisen in connection with the transfer of higher educational institutions to the remote mode of educational activities during the period of quarantine related to the COVID-19 pandemic are analyzed. Emphasis is placed on the attitude of teachers to the current situation. Both the rejection and the positive assessments of the remote learning format are related to the prospects for further organization of remote learning in its combination with the traditional format.